Public understanding of medical terminology: non-English speakers may not receive optimal care. Issue 2 (1st March 2000) - Cooke, M W; Wilson, S; Cox, P; Roalfe, A
Abstract : Introduction —Many systems of telephone triage are being developed (including NHS Direct, general practitioner out of hours centres, ambulance services). These rely on the ability to determine key facts from the caller. Level of consciousness is an important indicator after head injury but also an indicator of severe illness. Aims —To determine the general public's understanding of the term unconscious. Methods —A total of 700 people were asked one of seven questions relating to their understanding of the term unconscious. All participants were adults who could speak sufficient English to give a history to a nurse. Results —Correct understanding of the term unconscious varied from 46.5% to 87.0% for varying parameters. Those with English as their first language had a better understanding (p<0.01) and there was a significant variation with ethnicity (p<0.05). Conclusions —Understanding of the term unconscious is poor and worse in those for whom English is not a first language. Decision making should not rely on the interpretation of questions using technical terms such as unconscious, which may have a different meaning between professional and lay people.